2021
DOI: 10.1177/13548166211006988
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review on computable general equilibrium applications in tourism

Abstract: Assessment of the economy-wide impacts of tourism has increased importance due to the unprecedented impacts of COVID-19. Computable general equilibrium (CGE) approach is a versatile tool for estimating the economy-wide impacts of tourism, as opposed to alternative general equilibrium approaches and partial equilibrium approaches. However, there has not been any systematic review done on CGE applications in tourism literature. The article reviews CGE applications in tourism over the past 25 years using a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…The research found the crucial fact that the number of arrivals is a strong structural link to industrial viability widely. In 2020, the general equilibrium view of Thai tourism was explored by Wickramasinghe and Naranpanawa (2022) . This article primarily reviewed CGE applications in tourism over the past 25 years using a systematic quantitative literature review approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research found the crucial fact that the number of arrivals is a strong structural link to industrial viability widely. In 2020, the general equilibrium view of Thai tourism was explored by Wickramasinghe and Naranpanawa (2022) . This article primarily reviewed CGE applications in tourism over the past 25 years using a systematic quantitative literature review approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a systematic literature review, Wickramasinghe and Naranpanawa (2021) suggest the use of general equilibrium models to simulate policy interventions aiming at enhancing resilience in tourism. These models can capture the economy-wide impacts which include both direct and indirect economic consequences.…”
Section: Domestic Tourism and Tourism Crisesmentioning
confidence: 99%
“…The CGE approach is suitable. Wickramasinghe and Naranpanawa (2022) and Inchausti-Sintes (2015) reviewed recent CGE studies, most of which analyze spillover among industries. Other studies analyzed external impacts on tourism, such as climate change (Berrittella et al, 2006), bombing (Pambudi et al, 2009), and high-speed rail (Hiramatsu, 2018).…”
Section: Economic Effects Of Tourismmentioning
confidence: 99%
“…Under these conditions, equitable distribution of benefits from inbound tourism among urban and rural individuals has received scholarly attention (Shi et al, 2020) The tourism industry has gained popularity as an economic stimulant for less devel-©Southern Regional Science Association 2023. oped rural areas (Frederick, 1993;Briedenhann and Wickens, 2004); this is applicable in Japan, where the rural population is declining. Wickramasinghe and Naranpanawa (2022) emphasized the importance of computational general equilibrium (CGE) analysis to guide post-COVID tourism research. This study examines the contribution of the increase of inbound tourists to the growth of rural prefectures in Japan, which suffer from economic decline due to decreasing population.…”
Section: Introduction 1inbound Tourists and Decreasing Populationmentioning
confidence: 99%